2011
DOI: 10.1016/j.jastp.2011.01.003
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of uncertainties in monitoring middle atmosphere temperatures with the ground-based lidar network in support of space observations

Abstract: International audienceThe capability of the longest lidar data sets to monitor long-term temperature changes have been evaluated through comparisons with the successive Stratospheric Sounder Units (SSU) onboard NOAA satellites. Cross-consistency investigations between SSU and the lidar network can be considered as a first attempt to demonstrate how the synergistic use of space and ground-based instruments could provide reliable monitoring of the temperature of the middle atmosphere. The breakdown of the temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(65 citation statements)
references
References 47 publications
2
62
0
1
Order By: Relevance
“…[37] In B&L11 we have performed a detailed comparison with lidar measurements at the Observatory of HauteProvence in southern France (44 ı N) [Keckhut et al, 2011] and found very good agreement. Comparison with temperature trends derived from lidar measurements in the upper mesosphere/lower thermosphere at Fort Collins (41 ı N) published by She et al [2009] turns out to be more complicated since annually mean trends on geometrical altitudes for the period 1990-2007 are derived which makes it difficult to disentangle the geometrical/pressure altitude effect on trends in a height range where the background temperature gradient varies substantially with time and altitude.…”
Section: Comparison With Observationsmentioning
confidence: 96%
See 1 more Smart Citation
“…[37] In B&L11 we have performed a detailed comparison with lidar measurements at the Observatory of HauteProvence in southern France (44 ı N) [Keckhut et al, 2011] and found very good agreement. Comparison with temperature trends derived from lidar measurements in the upper mesosphere/lower thermosphere at Fort Collins (41 ı N) published by She et al [2009] turns out to be more complicated since annually mean trends on geometrical altitudes for the period 1990-2007 are derived which makes it difficult to disentangle the geometrical/pressure altitude effect on trends in a height range where the background temperature gradient varies substantially with time and altitude.…”
Section: Comparison With Observationsmentioning
confidence: 96%
“…Major progress has been achieved by analyzing long-term data records from groundbased, in situ, and satellite-borne measurements [see, for example, She et al, 2009;Keckhut et al, 2011;Kubicki et al, 2006;Keating et al, 2000]. Since the pioneering work of Roble and Dickinson [1989], extensive modeling has helped to identify the main reasons responsible for these trends, namely the increase of greenhouse gasses (GHG) [e.g., Akmaev et al, 2006;Schmidt et al, 2006;Garcia et al, 2007].…”
Section: Introductionmentioning
confidence: 99%
“…Within the framework of the Atmospheric dynamics Research and InfraStructure in Europe (ARISE, http://arise-project.eu) project, a recent study has focused on comparisons between measurements from ground-based facilities and ECMWF analysis models over the time span ranging from July 2012 to May 2013. Measurements from colocated Rayleigh scatter lidar (temperature in the 30-70 km range [Keckhut et al, 2011]), mesospheric airglow (temperature around the mesopause region [Schmidt et al, 2013]), and Doppler radiometer (horizontal winds between 40 and 70 km [Rüfenacht et al, 2012]) facilities have been compared to the ECMWF analysis (up to 78 km altitude). It has been found that significant biases in temperatures and horizontal winds exist, primarily at higher altitudes and at shorter timescales.…”
Section: 1002/2014jd021632mentioning
confidence: 99%
“…Some differences with other lidar series have been reported [2] as well as differences between summer and winter estimates ( Figure 1). …”
Section: Figure 1 Temperature Trends Derived From the Ohp Lidar For mentioning
confidence: 68%
“…While the continuity suffers from tidal effect due to the orbit changes from the successive satellites and their time drifting [2], the continuity is now insured by AMSU. Comparisons between lidar and AMSU reveal very good agreements when data obtained on the same days are considered and partial sampling appear critical [3].…”
Section: Ssu and Amsu Continuitymentioning
confidence: 99%